A novel mutation in COL3A1 associates to vascular Ehlers–Danlos syndrome with predominant musculoskeletal involvement. Issue 9 (28th July 2021) - Ruscitti, Federica; Trevisan, Lucia; Rosti, Giulia; Gotta, Fabio; Cianflone, Annalia; Geroldi, Alessandro; Origone, Paola; Pichiecchio, Anna; Viglio, Simona; Iascone, Maria; Mandich, Paola
Abstract: Background: Vascular Ehlers–Danlos syndrome (vEDS) is a heritable connective tissue disorder caused by defects in the type III collagen protein. It is generally considered the most severe form of Ehlers–Danlos syndrome (EDS) due to an increased risk of spontaneous artery or organ rupture. vEDS has an extremely heterogeneous presentation and muscle rupture is considered a minor diagnostic criterium. Methods: A patient with a long history of inconclusive examinations and investigations was referred to our unit. The clinical picture was mainly characterized by muscle ruptures, whereas the cardiovascular involvement was limited to mitral regurgitation. We performed a panel analysis of genes associated with inheritable heart diseases using the TruSight Cardio kit (Illumina). A skin biopsy was then performed for functional studies to analyze the different forms of collagen molecules produced in vitro by cutaneous fibroblasts. Results: The patient presented the novel variant c.3478A>G (p.Ile1160Val) in COL3A1 (NM_000090.3), whose pathogenicity was supported by biochemical analysis of type III collagen. Conclusion: In this report, we describe a case of vEDS with predominant and severe musculoskeletal involvement. Our findings provide insight into genetic variants and clinical expression of vEDS, broadening the clinical scenario of the syndrome. Abstract : In this report, we describe a case of vEDS with predominant and severe musculoskeletal involvement. Our findings provide insight into genetic variants and clinical expression of vEDS, enlarging the clinical scenario of the syndrome.